The October 1891 Cartago (Costa Rica) floods from documentary sources and 20CR data - Amador Astúa, Jorge Alberto (2018)
This work comes to fill a fundamental gap in the history of Central American extreme climatic events by putting together qualitative and quantitative historical data and reanalysis information (the 20CR project) for the reconstruction of meteorological events associated with the floods that destroyed Cartago City in Costa Rica on October 27, 1891. This is a case study of a devastating 19th‐century disaster with profound social repercussions. Accounts, original historical documents, artistic depictions, instrumental data and photographs of the floods provide enough evidence of the severity of the meteorological system and the social dimension of the disaster. The historical information details the continuous rains, as well as the area covered by mud, trees and big rocks in the Cartago Valley due to the Reventado River flooding. Based on the above sources, the destruction of houses, roads and civil infrastructure is described, and the meteorological conditions of the period are analysed. By using documentary, instrumental and 20CR data, the potential direct or indirect effects of some tropical atmospheric systems were studied for the period October 22–29, 1891. Results indicate that the most probable cause of the rains and floods was a Caribbean “temporal,” a system that strikes the region frequently. This phenomenon, according to 20CR data, was modulated by a high‐pressure system over the Gulf of Mexico and brought abundant moisture and high winds to the region. Two women and three children were officially confirmed to have died; however, other sources imply many more victims and disappearances. The interventions by the government and local people were crucial for the restoration of the flooded part of Cartago City from the tragedy. The rains and floods left more than 120 seriously damaged or destroyed houses, and severe economic losses equivalent to potentially much more than 49 MM U.S. dollars.